Audit Energi Sistem Tata Cahaya dan Tata Udara Rumah Makan di Kota Pekanbaru - Awaludin Martin (Proksima, 2023)
An energy audit is a method for calculating the level of energy use of a building or buildings, in which the results will be compared with existing standards and then look for solutions to save energy consumption if the level of energy consumption exceeds the standard. The purpose of an energy audit is to reduce energy use and save costs in energy use. In this research, energy audits were carried out at restaurants in Pekanbaru City. The method used is a quantitative method including calculating the use of electricity in lighting and air conditioning systems, Calculating Energy Consumption Intensity (IKE), and Energy Conservation Opportunities (ECO). Based on the results of the study, the IKE value was obtained before saving was 11.03 in the efficient category. After saving, IKE fell to 5.42 in the very efficient category. The electricity that can be saved in a year from this restaurant is 48,234.4 kWh with a total cost of Rp. 69,684,284.